Eclipta prostrata (L.) L. (Asteraceae): Ethnomedicinal Uses, Chemical Constituents, and Biological Activities - Deepak Timalsina (MDPI AG, 2021)
Eclipta prostrata (L.) L. (Syn.: Eclipta alba (L.) Hassak, Family: Asteraceae) is an important medicinal plant in the tropical and subtropical regions. It is widely used in treating various diseases of skin, liver and stomach in India, Nepal, Bangladesh, and other countries. The main aim of this review was to collect and analyze the available information on traditional uses, phytoconstituents, and biological activities of E. prostrata. The scientific information was collected from the online bibliographic databases such as Scopus, MEDLINE/PubMed, Google Scholar, SciFinder, etc. and books and proceedings. The active phytochemicals were coumestan derivatives, phenolic acid derivatives, flavonoids, triterpenoid and steroid saponins, substituted thiophenes, etc. Various extracts and isolated compounds of E. prostrata showed a wide range of biological activities such as antimicrobial, anticancer, hepatoprotective, neuroprotective and hair growth promoting activities. Relatively a few studies have been performed to reveal the exact phytoconstituents responsible for their corresponding pharmacological activities. Future studies should focus on detailed mechanism based studies using animal models and clinical studies.